Einfluss der subdekadischen NAO Variabilität auf die Temperatur im Nordatlantik - Rehberg, Maya (2018)
The ocean and the atmosphere form the components of the climate system of the earth with the highest variability. In both systems, internal processes lead to periodic oscillations of the variables of state. A deeper understanding of the interaction between the ocean and the atmosphere is necessary to optimize climate models. This thesis deals with the subdecadal variability of the North Atlantic Oscillation (NAO), and its impact on the potential temperature and the heat content in the Atlantic Ocean. A Singular Spectrum Analysis (SSA) of the wintertime NAO-Index from 1864 to 2017 after Hurrell (2003) results in a subdecadal mode with a periodicity of 8 years, which makes up to 20% of the total variability. In the period from 1900 to 1959, a shorter mode of 6 years is dominating. Lag regressions of the subdecadal mode on horizontal and vertical planes of the potential temperature reveal an impact of the subdecadal mode of the NAO on the depth subtropical and subpolar gyre. This relationship is clearly recognizable when considering only data since 1960. The correlation of the subtropical and subpolar gyre with the N AO has an opposite prefix. Therefore an investigation of a Gyre Index, defined as the difference between the heat contents of the gyres, is performed. The correlation of the subdecadal mode of the NAO with the ocean heat content of the subtropical gyre is bigger than the correlation with the Gyre Index. Including the subpolar gyre does not lead to a higher correlation.